2021
DOI: 10.21203/rs.3.rs-871619/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ten-Year Trends of Adult Trauma Patients in Denmark from 2010 to 2019: A Retrospective Cohort Study

Abstract: Background: Trauma causes a considerable economic and societal burden and the trauma patient population and its prognosis changes over time. The aim of this study is to analyze ten-year trends of trauma patients at a major trauma center in Denmark. Methods: 5366 patients aged ≥ 16 years with Injury Severity Score (ISS) > 0 admitted by trauma team activation at Aarhus University Hospital Trauma Center between January 1, 2010 and December 31, 2019 were included. Descriptive statistics, incidence rate calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…In two-wheeler accidents motorcycle accidents, bicycle and scooter accidents were observed. The findings are similar to a study in which 26% patients had two-wheeler accidents out of which bicycle accidents were commonest followed by motorcycle injuries 17 .…”
Section: Fig 3: Gcs Score Of Patients (N=305)supporting
confidence: 88%
See 3 more Smart Citations
“…In two-wheeler accidents motorcycle accidents, bicycle and scooter accidents were observed. The findings are similar to a study in which 26% patients had two-wheeler accidents out of which bicycle accidents were commonest followed by motorcycle injuries 17 .…”
Section: Fig 3: Gcs Score Of Patients (N=305)supporting
confidence: 88%
“…The mechanism of injury in the study, fall from height followed by fall at home, pedestrian, assault, gunshot shot and others. The findings were similar in study by Frederik Trier et al, like fall (20.3%) is commonest followed by pedestrian injury (5.5%), violence (5.2%), stabbing (2.9%) and gunshot (0.5%) 17 . Other study in Ethiopia showed that fall down was commonest (23.5%) followed by fighting, (31.8%), machine injury (9.4%), stab injury (3%) and burn (1.1%) 14 .…”
Section: Fig 3: Gcs Score Of Patients (N=305)supporting
confidence: 87%
See 2 more Smart Citations